Integrating Restorative Justice into Mineral and Coal Mining Crime Resolution: A Normative Analysis for Sustainable Development in Indonesia - Rosyanto Yudha Hermawan; M. Hadin Muhjad; Rachmadi Usman (Journal of Social Work and Science Education, 2026)
This study analysed the settlement of mineral and coal mining criminal acts through a restorative justice approach as an alternative to the conventional criminal justice system as well as It seeks to identify the distinctive characteristics of equitable settlement mechanisms and to develop a reformulated model that aligns with the principles of sustainable mining development. Using a normative juridical (doctrinal) research method, the study examines statutory regulations, judicial decisions, and scholarly works related to the settlement of mining crimes. The analysis involves both primary and secondary legal materials to evaluate the coherence between current legal norms and restorative principles. A prescriptive approach is applied to propose legal reform aimed at integrating restorative mechanisms into the mining law framework. Findings revealed that the Mining Law primarily focuses on punitive measures and has yet to regulate restorative justice mechanisms. Mining-related offenses encompass illegal mining, false data submission, failure to reclaim, and environmental destruction. The study shows that applying restorative justice through penal mediation, restorative conferences, and community-based dialogue can accelerate resolution, reduce costs, and address victims’ needs while restoring social harmony. It provides a framework for government institutions to mediate mining disputes effectively while ensuring social and ecological recovery. The study contributes to the advancement of legal scholarship by bridging restorative justice theory with mining governance. It establishes a foundation for formulating future legal reforms that emphasize comprehensive, fair, and sustainable approaches to resolving mining-related criminal cases.